Memuary Anny Jewdokimowny Łabziny – przyczynek do poznania obyczajowości kobiety rosyjskiej końca XVIII wieku - Grażyna Waliszewska (Studia Rossica Posnaniensia)
Anna Labzina, born in the eighteenth century in a gentry family, left extraordinary memoirs. Her diaries are not a testimony of time but rather reflect her very own experiences and emotions connected with her unsuccessful marriage, a decision which was made when she was thirteen years old. Her notes confirm the eighteenth-century principle of absolute dependence on one’s husband. Labzina accepts and suffers dependence meekly, but from her words the picture of a “pained soul” emanates – the only thing she can rebel against is her fate.